Quantitative Comparisons on the Intrinsic Features of Foreign Exchange Rates Between the 1920s and the 2010s: Case of the USD-GBP Exchange Rate - Young Wook Han (East Asian Economic Review (EAER), 2016)
This paper quantitatively compares the intrinsic features of the daily USD-GBP exchange rates in two different periods, the 1920s and the 2010s, under the same freely floating exchange rate system. Even though the foreign exchange markets in the 1920s seem to be much less organized and developed than in the 2010s, this paper finds that both the long memory volatility property and the structural break appear to be the common intrigue features of the exchange rates in the two periods by using the FIGARCH model. In particular, the long memory volatility properties in the two periods are found to be upward biased and overstated because of the structural breaks in the exchange markets. Thus this paper applies the Adaptive-FIGARCH model to consider the long memory volatility property and the structural breaks jointly. The main finding is that the structural breaks in the exchange markets affect the long memory volatility property significantly in the two periods but the degree of the long memory volatility property in the 1920s is reduced more remarkably than in the 2010s after the structural breaks are accounted for; thus implying that the structural breaks in the foreign exchange markets in the 1920s seem to be more significant.
Keywords: C22; E44; F31; 330; The 1920s; Daily USD-GBP Exchange Rates; Long Memory Volatility Property; Structural Breaks; FIGARCH Model; Adaptive FIGARCH Model